2015
DOI: 10.3126/jcmsn.v11i1.13314
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception regarding dental aesthetics, knowledge and attitude of traumatic dental injury and halitosis among people of Aurabani, Sunsari district of Eastern Nepal

Abstract: Background and Objectives: Incr eased concer n over dental appearance has been observed during childhood and adolescence to early adulthood. The study was conducted with objectives to assess the selfperception of dental aesthetics, knowledge, attitude and management of dental trauma and halitosis. Materials and Methods: Self-administered questionnaire translated in Nepali language consisting of 32 questions was used. The completed questionnaires were analyzed using descriptive statistics. Results: Out of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Bad breath or halitosis was stated as dental problem by 46.64% of this total sample while another study in a similar location found that 57.74% had this problem. 12 In this study, "no brushing cause's dental caries" was reported by significantly more individuals from the privileged group which was reflected on their habit of using toothbrushes. This finding is comparable to a study on school-aged children from China.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Bad breath or halitosis was stated as dental problem by 46.64% of this total sample while another study in a similar location found that 57.74% had this problem. 12 In this study, "no brushing cause's dental caries" was reported by significantly more individuals from the privileged group which was reflected on their habit of using toothbrushes. This finding is comparable to a study on school-aged children from China.…”
Section: Discussionmentioning
confidence: 60%
“…9 Many studies pertaining to oral health status that have been carried out in Nepal mainly target the school-aged children, elderly or pregnant women. [10][11][12][13][14] Poor and marginalized people in Nepal have higher proportion of oral health problems. 15 A large-scale study suggested that only 10% of Nepalese adults brush twice daily and only about 4% reported visiting dentists within the last six months.…”
Section: Introductionmentioning
confidence: 99%